CONVERSATIONAL METHOD PADA PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA ARAB - Baiq Tuhfatul Unsi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Speaking Arabic skills are language skills that must be possessed by students in order to develop foreign language skills, in this case especially Arabic. In relation to teaching Arabic, one method that can be used to improve students' speaking skills is the Conversational Method. The Conversation Method is a way of presenting Arabic learning material through conversation or dialogue, both between students and between students and teachers, as well as to add to the vocabulary of Arabic. This paper focuses on the application of the Conversational Method in learning Arabic speaking skills, the students' Arabic speaking skills as well as the inhibiting and supporting factors of the application of the Conversational Method in learning Arabic speaking skills of students. The results of this study are that the application of the conversational method in learning Arabic speaking skills for students of MIN Bendunganjati is through three stages, namely the preliminary stage, the implementation stage in the form of simple conversations between students and teachers and students and students. and the evaluation stage. In general, MIN Bendunganjati students are able to speak Arabic, this is evidenced by the activeness and enthusiasm of students in communicating Arabic in class. As for the inhibiting factors in the application of the conversational method, namely: Lack of basic Arabic skills possessed by students due to differences in their potential and abilities. While the supporting factors are: school environment, facilities/infrastructure and the role of teachers.